CD14+ CD16+ monocytes rather than CD14+ CD51/61+ monocytes are a potential cytological marker of circulating osteoclast precursors in multiple myeloma. A preliminary study. (24th March 2014) - Petitprez, V.; Royer, B.; Desoutter, J.; Guiheneuf, E.; Rigolle, A.; Marolleau, J. P.; Kamel, S.; Guillaume, N.
Summary Introduction Osteolytic bone destruction is a major clinical problem in multiple myeloma patients. Osteoclasts can differentiate in vitro from bone marrow‐resident monocyte progenitors, such as common monocyte progenitors, as well as circulating monocytes. Various types of monocytes, including osteoclast precursors, appear to circulate systemically. Methods We investigated the possibility of demonstrating, by in vitro differentiation and flow cytometry, a circulating osteoclast precursor population in multiple myeloma (MM) patients by studying the distribution of CD14+/++ CD11b+ CD51/61+ and CD14+/++ CD16+/− populations. Results Under short‐term in vitro osteoclastic differentiation conditions, almost all CD14 monocytes acquired CD51/61 and CD16 expression. Flow cytometry studies failed to demonstrate a statistically significant increase in circulating CD14+/++ CD11b+ CD51/61+ populations in 20 MM patients with osteolytic lesions. However, the minor circulating CD14+/++ CD16+ fraction was significantly increased in MM patients compared with healthy volunteers (109.3 ± 63.1/mm3vs. 65.3 ± 34.9/mm3; P = 0.005), but with no correlation with markers of tumour burden. The CD14+/++ CD16+ to CD14+/++ CD16− ratio was higher in MM patients. Conclusion The circulating CD14+/++ CD11b+ CD51/61+ fraction was not correlated with bone lesions in MM patients. However, CD14+/++ CD16+ monocytes may be a candidate marker. A larger study must be conducted to confirm these promising results for the diagnosis and follow‐up of MM patients.